Risk Factors for Positive Follow-Up Blood Cultures in Gram-Negative Bacilli Bacteremia: Implications for Selecting Who Needs Follow-Up Blood Cultures. (28th March 2020) - Mitaka, Hayato; Gomez, Tessa; Lee, Young Im; Perlman, David C
Abstract: Background: The value of follow-up blood cultures (FUBCs) to document clearance of bacteremia due to Gram-negative bacilli (GNB) has not been well established. Although previous studies suggested that the yield of FUBCs for GNB bacteremia is low, it remains to be elucidated for whom FUBC may be beneficial and for whom it is unnecessary. Methods: A retrospective cohort study was performed at 4 acute care hospitals to identify risk factors for positive FUBCs with GNB bacteremia and to better guide clinicians' decisions as to which patients may or may not benefit from FUBCs. Participants included adult patients with GNB bacteremia who had FUBCs and were admitted between January 2017 and December 2018. The primary outcomes were the factors associated with positive FUBCs and the yield of FUBCs with and without the factors. Results: Of 306 patients with GNB bacteremia who had FUBCs, 9.2% (95% confidence interval, 6.2%–13.0%) had the same GNB in FUBCs. In the multivariate logistic regression analysis, end-stage renal disease on hemodialysis, intravascular device, and bacteremia due to extended-spectrum β-lactamase or carbapenemase-producing organism were identified as independent predictors of positive FUBCs with GNB bacteremia. Approximately 7 FUBCs and 30 FUBCs were needed for patients with ≥1 or no risk factors, respectively, to yield 1 positive result. SummaryThis multi-site retrospective cohort study found that among patients with gram-negative bacilli (GNB) bacteremia, having ESRD on hemodialysis, intravascular devices, or bacteremia due to multi-drug resistant GNB were each independently associated with having a positive follow-up blood culture. Conclusions: Follow-up blood culture may not be necessary for all patients with GNB bacteremia and has the highest yield in patients with 1 or more risk factors.